A aula de campo como alternativa metodológica para o ensino de Ciências visando uma aprendizagem significativa - Barbosa, Juliana Araujo do Carmo Sales (2013)
The class field is an important issue in the teaching of Natural Sciences; despite this importance such methodology is not widely used, or wrongly applied by the teachers who use it. Based on this premise this paper studied the methodologies used by teachers of Natural Sciences State School Joaquim Augusto da Costa Marques municipality of Denise MT; systematizing the practice of field classes. We work from the perspective of conceptual construction focused on meaningful learning, critical and reflective. From reflections emerged ace new contributions to teaching and learning, presenting an alternative school that is opposed to traditional teaching. This study used a qualitative methodology, and data collection was carried out through interviews with ten school teachers mentioned above. From these data it was proposed didactic material on the practice field classes (manual of procedures and theory of teaching and learning, focusing on significant critical theory and reflexive). With the results that can be seen is that teachers do not feel comfortable in using new methodologies. From this evidence constituted a study group in which teachers would gather once a week to undertake the study of the teaching material, and from the discussions were made notes on how to use the methodology of field class. From the results obtained it has evidence that the teaching material prepared on field classes was able to encourage teachers to redesign their teaching practices with a view to a more effective teaching and learning more meaningful for the student, together with the context, criticality, reflection, autonomy and taste for school and science.